Does Baseline Serum Androgen Levels Have an Impact on Ovulation Induction Cycle Outcomes by Using Clomifene Citrate among Infertile Women with Polycystic Ovary Syndrome? A Retrospective Cohort Study - Kahyaoglu, Serkan; Ozaksit, Muzeyyen Gulnur; Karacan Duman, Gozde; Ozturk Atan, Deniz; Kahyaoğlu, Inci; Kuru Pekcan, Meryem; Moraloglu Tekin, Ozlem (Gynecology Obstetrics & Reproductive Medicine, 2023)
OBJECTIVE: Hyperandrogenism is one of the diagnostic criteria for polycystic ovary syndrome. Women with polycystic ovary syndrome suffer from infertility due to anovulation. Hyperandrogenism results in follicular arrest at the antral stage during folliculogenesis. baseline intrinsic hyperandrogenism affects the success of ovulation induction or not. The relationship between baseline serum androgen levels and ovulation induction cycle outcomes by using clomifene citrate among infertile women with polycystic ovary syndrome has not been investigated thoroughly. STUDY DESIGN: Ovulation induction cycle outcomes of 35 infertile women diagnosed with polycystic ovary syndrome according to Rotterdam criteria who have received 50-100 mg/day clomifene citrate have been evaluated retrospectively. Menstrual cycle day 2-5 serum levels for gonadotropins, androgens, metabolic parameters, and ovulation induction cycle outcomes have been compared between women who have and have not achieved clinical pregnancy following treatment. RESULTS: Serum basal follicular stimulating hormone, LH, E2, fasting cholesterol, glucose, and HOMA-IR levels were comparable between these two groups of patients. Unlike other serum androgens, baseline serum-free testosterone level is significantly lower for patients who have achieved clinical pregnancy following ovulation induction with clomifene citrate. The baseline serum cut-off level for free testosterone to predict clinical pregnancy was 1.94 pg/ml with 75% sensitivity and 67% specificity rates. CONCLUSION: Lower or higher levels of androgenic milieu within the ovaries result in defective folliculogenesis and ovulation failure. Increased serum levels of free testosterone which is a proxy for ovarian androgen production might be a detrimental factor for clinical pregnancy rates of women with polycystic ovary syndrome by impairing proper folliculogenesis.